Care-educational game for men who have sex with men and live with HIV and Aids - Mariano, Maria Tereza Leite; Leite, Márley Romão; Mandelli, Bárbara Furtado; Nascimento, Maria Mônica Paulino do; Fernandes, Marcelo Costa; Temoteo, Rayrla Cristina de Abreu; Silva, Cícera Renata Diniz Vieira (Revista de Enfermagem da UFPI, 2024)
Objective: To describe the construction of a board game-type care-educational technology for the health education of men who have sex with men and live with the Human Immunodeficiency Virus and Acquired Immunodeficiency Syndrome, within the scope of Primary Health Care. Methods: Methodological study, developed from a participatory perspective in four stages: development of a scoping review; theorization and construction of the technology; appraisal; and final design. Results: The game “HIVIVENDO E APRENDENDO” was constructed considering the integrative perspective of care for the target population, addressing in its content aspects about the infection and the disease, welcoming, treatment adherence, related stigmas and prejudices, citizenship, and quality of life. Conclusion: With the developed care-educational technology, it is intended that, after the validation phase, it can become a facilitating tool for promoting health education for both professionals and users in Primary Health Care.